2014
DOI: 10.1111/ecot.12061
|View full text |Cite
|
Sign up to set email alerts
|

Services liberalization and productivity of manufacturing firms

Abstract: Employing a unique database of Ukrainian firms in 2001-07, we use the external push for liberalization in the services sector as a source of exogenous variation to identify the effect of services liberalization on total factor productivity (TFP) of manufacturing firms. The results indicate that a standard deviation increase in services liberalization within a firm is associated with a 9.2 percent increase in TFP. The effect is stronger for firms with high productivity, bringing about a reallocation of resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Most recently, Shepotylo and Vakhitov (2015) employed a large database of Ukrainian firms in [2001][2002][2003][2004][2005][2006][2007] to identify the effect of services liberalization on total factor productivity (TFP) of manufacturing firms. The results indicated that an increase in services liberalization was associated with an increase in TFP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most recently, Shepotylo and Vakhitov (2015) employed a large database of Ukrainian firms in [2001][2002][2003][2004][2005][2006][2007] to identify the effect of services liberalization on total factor productivity (TFP) of manufacturing firms. The results indicated that an increase in services liberalization was associated with an increase in TFP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Earle et al (2014) demonstrated that political favouritism combined with weak institutions had a substantial redistributional impact on productivity. Most recently, Kim et al (2015) demonstrated that overall improvements in firm productivity within Ukraine's manufacturing sector were found to vary substantially by industry, trade status and firm turnover; while Shepotylo and Vakhitov (2015) identified the effect of service liberalization on the TFP of manufacturing firms. However, so far no attempts have been made to study, empirically, the relationship between productivity and firm characteristics of Ukrainian enterprises in particular regions.…”
mentioning
confidence: 99%
“…3 Finally, Freund and Bolarky (2008) find 2 See Francois and Hoekman (2010) for a survey of the theory and more than a dozen empirical studies that support this finding. Additionally, in recent years, several studies that use firm-level data support this finding including Arnold, Javorcik, and Mattoo (2011) for the Czech Republic, Fernandes and Paunov (2012) for Chile, Arnold, Javorcik, Lipscomb, and Mattoo (2016) for India and Shepotylo and Vakhitov (2015) for Ukraine. that trade promotes growth in countries with good institutions, but trade did not increase growth among countries with bad institutions (countries with bad institutions are those that are in the worst quartile of their excessive regulations index).…”
mentioning
confidence: 74%